Burkholderia mimosarum sp. nov., isolated from root nodules of Mimosa spp. from Taiwan and South America - Chen, W.M.; James, EK; Coenye, T.; Chou, JH; Barrios, E.; Faria, S.M. de; Elliott, G.N.; Sheu, SY; Sprent, JI; Vandamme, P (Microbiology Society, 2006)
Fourteen strains were isolated from nitrogen-fixing nodules on the roots of plants of the genus Mimosa growing in Taiwan, Brazil and Venezuela. On the basis of 16S rRNA gene sequence similarities, all of the strains were previously shown to be closely related to each other and to belong to the genus Burkholderia. A polyphasic approach, including DNA–DNA reassociation, whole-cell protein analysis, fatty acid methyl ester analysis and extensive biochemical characterization, was used to clarify the taxonomic position of these strains: all 14 strains were classified as representing a novel species, for which the name Burkholderia mimosarum sp. nov. is proposed. The type strain, PAS44T (=LMG 23256T =BCRC 17516T), was isolated from Mimosa pigra nodules in Taiwan.